Parlamentskii chas . Parlamentskii chas . Parliamentary Hour . Парламентский час - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Opening of the Parliament TV-center; commentary on the minimal wage indexation law; discussion of Russian scientific development programs; partition of the Black Sea Fleet between Ukraine and Russia; the status of Sevastopol; development issues of art and cinema. Открытие парламентского телецентра; комментарий к закону об индексации минимальной оплаты труда; обсуждение программ развития науки в России; раздел Черноморского флота между Украиной и России, статус города Севастополя; проблемы развития искусства и кинематографа.